1995
DOI: 10.1128/jb.177.1.20-26.1995
|View full text |Cite
|
Sign up to set email alerts
|

Dihydroxylation and dechlorination of chlorinated biphenyls by purified biphenyl 2,3-dioxygenase from Pseudomonas sp. strain LB400

Abstract: Oxidation of biphenyl and nine chlorinated biphenyls (CBs) by the biphenyl 2,3-dioxygenase from Pseudomonas sp. strain LB400 was examined. The purified terminal oxygenase required the addition of partially purified electron transport components, NAD(P)H, and ferrous iron to oxidize biphenyl and CBs. cis-Biphenyl 2,3-dihydrodiol was produced with biphenyl as the substrate. Dihydrodiols were produced from all CBs, and more than one compound was produced with most substrates. Catechols were produced when the diox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
125
3

Year Published

1997
1997
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 138 publications
(139 citation statements)
references
References 29 publications
11
125
3
Order By: Relevance
“…Thus, when 2,2',3,3',6,6'-hexachlorobiphenyl was degraded in the chemostat culture experiments it is likely that 3,4-dihydroxy 3,4-dihydro-(2,2',3',5,6,6'-hexachloro)biphenyl was the end product. Accumulation of 3,4-dihydroxy 3,4-dihydro(nchloro)biphenyls in resting-cell assays has been reported by Nadim et al (1987) and in enzyme assays by Haddock et al (1995). Alternatively, 3,4-dihydroxy (2,2',3',5,6,6'-hexachloro)biphenyl might be the endproduct of 2,2',3,3',6,6'-HCB degradation in JB 1.…”
Section: Discussionmentioning
confidence: 70%
See 2 more Smart Citations
“…Thus, when 2,2',3,3',6,6'-hexachlorobiphenyl was degraded in the chemostat culture experiments it is likely that 3,4-dihydroxy 3,4-dihydro-(2,2',3',5,6,6'-hexachloro)biphenyl was the end product. Accumulation of 3,4-dihydroxy 3,4-dihydro(nchloro)biphenyls in resting-cell assays has been reported by Nadim et al (1987) and in enzyme assays by Haddock et al (1995). Alternatively, 3,4-dihydroxy (2,2',3',5,6,6'-hexachloro)biphenyl might be the endproduct of 2,2',3,3',6,6'-HCB degradation in JB 1.…”
Section: Discussionmentioning
confidence: 70%
“…It is possible that energy may have to be invested in the first steps of aerobic PCB metabolism. Indeed, Haddock et al (1995) showed that the biphenyl 2,3-dioxygenase from Pseudomonas sp. LB400 required the addition of NAD(P)H and reduced iron (Fe2+).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, only in a few cases has direct or indirect evidence for such a reaction been obtained. Haddock et al (1995), working with BphA-LB400, reported, on the grounds of GC-MS data, the likely 3,4,3',4'-bis-DHD formation exclusively from 2,5,2',5'-tetrachlorobiphenyl among a range of chlorobiphenyls investigated. Kimura et al (1996), studying biotransformations by the mutant strain Pseudomonas sp.…”
Section: Direct and Indirect Evidences For Double Dioxygenationsmentioning
confidence: 99%
“…As this modulation critically depends on the active site architecture, it should be enzyme-specific. With the ARHDO catalytic mechanism outlined above, observations like the preferred dioxygenations of 2,2'-dichlorobiphenyl at carbons 2 and 3 (Haddock et al 1995;Seeger et al 1995) and the double dioxygenation of 2,5,2',5'-tetrachlorobiphenyl (Haddock et al 1995) appear difficult to be interpreted alone by electronic influences on the reaction mechanism. This is underpinned by the findings that these specific dioxygenations are shown only by some ARHDOs, but not by others that accept these substrates.…”
Section: Potential Reasons For Failures Of Double Dioxygenationsmentioning
confidence: 99%